PENGARUH VARIASI PENAMBAHAN KADAR AIR DENGAN BAHAN PENGIKAT BENTONIT TERHADAP KARAKTERISTIK PASIR CETAK DAN CACAT POROSITAS HASIL PENGECORAN LOGAM PADUAN Al-Si - Fajar Rizki Saputra; Budi Harjanto; Nyenyep Sriwardani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2020)
The purposes of this research was to learns (1) the effect of adding moisture content to the permeability of sand casting; (2) the effect of adding moisture content to the compressive strength of sand casting; and (3) the effect of adding moisture content to porosity defects in casting results. This research is conducted at Manufacturing Polytechnic, Ceper, Klaten. The method that used is pre-experimental design with design one-shot case study. The independent variable in this research are variations of moisture content of 4%, 6%, and 8%, with the dependent variable are permeability and compressive strength of sand casting, and porosity defect of Al-Si alloy cast. The permeability test by using permeability meter, compressive strength test by using universal strength machine¸ and porosity defect test of cast result on qualitative with visual observation and quantitative with calculation of porosity percentage. The results of the adding of moisture content of 4%, 6%, and 8% in the sand casting showed that: (1) The higher the addition of water measure on sand casting decrease the permeability value. The highest permeability value in the addition of 4% water measure is 103.67 cm3/min, while the lowest in the addition of 8% water measure is 83.00 cm3/min; (2) The higher water content in the printed sand further decreases the value of its compressive strength. The lowest compressive strength value occurred at 8% water measure increase of 39.00 KN/m2, while the highest value of compressive strength was obtained at 4% water measure addition 47.56 KN/m2; (3) The higher water measure of sand casting will result in a higher percentage of porosity defects on the casting results. The lowest percentage of porosity defect was obtained by adding 4% water measure is 1.56% from total volume, while the highest was 8% water measure is 3.06% from total volume.